2017
DOI: 10.1039/c6dt04900a
|View full text |Cite
|
Sign up to set email alerts
|

Photomagnetic properties of an Fe(ii) spin-crossover complex of 6-(3,5-diamino-2,4,6-triazinyl)-2,2′-bipyridine and its insertion into 2D and 3D bimetallic oxalate-based networks

Abstract: The Fe(ii) complex of the L ligand (L = 6-(3,5-diamino-2,4,6-triazinyl)-2,2'-bipyridine) has been used as a templating cation for the growth of oxalate-based networks. The magnetic characterization of the [Fe(L)](ClO)·CHCN (1) precursor in the solid state has been performed for the first time showing that the low-spin (LS) state is predominating from 2 to 400 K with 10% of Fe(ii), which undergoes a gradual and irreversible spin-crossover above 350 K. 1 presents the LIESST effect with a photo-conversion close t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 75 publications
1
13
0
Order By: Relevance
“…This could indicate that they present a higher T 0 (close to 170 K) or that T(LIESST) of compounds with high T 1/2 deviates significantly from that formula as observed for other Fe(II) with tridentate ligands. 19 Very recently, it has been proposed that a complicated relationship between T(LIESST) and T 1/2 may reflect low-temperature thermal and lightinduced symmetry breaking.…”
Section: +mentioning
confidence: 99%
“…This could indicate that they present a higher T 0 (close to 170 K) or that T(LIESST) of compounds with high T 1/2 deviates significantly from that formula as observed for other Fe(II) with tridentate ligands. 19 Very recently, it has been proposed that a complicated relationship between T(LIESST) and T 1/2 may reflect low-temperature thermal and lightinduced symmetry breaking.…”
Section: +mentioning
confidence: 99%
“…It is however consistent with the behavior observed in other compounds with T 1/2 well above room temperature, which also deviate from this formula. 21,[35][36][37] Deposition on substrates. In the last years, many studies have been focused on the charge transport properties of SCO compounds on surfaces as a first step prior to their integration into devices.…”
mentioning
confidence: 99%
“…In a previous work, we showed that the [Fe II (L) 2 ] 2+ complex with L = (3,5-diamino-2,4,6-triazinyl)2,2′-bipyridine (see Scheme 1) 19 stabilized both a 2D oxalate network and a chiral 3D structure. 20 Interestingly, the [Fe II (L) 2 ](ClO 4 ) 2 ·CH 3 CN precursor exhibited a photo-induced spin transition. 20…”
Section: Introductionmentioning
confidence: 99%
“…20 Interestingly, the [Fe II (L) 2 ](ClO 4 ) 2 ·CH 3 CN precursor exhibited a photo-induced spin transition. 20…”
Section: Introductionmentioning
confidence: 99%